The recent advances in Vascular endothelial growth factor and metabolic syndrome in prostate cancer - Zhou, Ya-nan; Song, Jin-qi; Tu, Gang-liang; Xu, Hui; Ding, Meng (Nepalese Journal of Cancer, 2021)
Prostate cancer is one of the most common male malignant tumors in Western countries. In the United States, there are about 170,000 new cases of prostate cancer in 2019, ranking second only to lung cancer.1, 2 In recent years, the incidence of prostate cancer in China is gradually increasing occupying the third place among male urogenital malignancies. The metastasis of prostate cancer mainly depends on blood vessels and lymphatic vessels, and the late discovery and poor prognosis of patients are the main reasons for the high fatality rate.2 Relevant epidemiological studies on immigration have found that the incidence of PCa in The Asian population in the United States is as high as 77.8 / l0000, which is similar to local residents and significantly higher than that in the native population in Asia. This suggests that, in addition to race and family history, different diet and lifestyle in China and the West may play an important role in the development and progression of PCa.3 Epidemiological studies have shown an association between geographic location and prostate cancer risk. In fact, the incidence of prostate cancer in Western men is 15 times higher than in Asian men. This suggests that environmental factors or lifestyle, especially diet and nutrition, may play a key role in the occurrence and development of prostate cancer.4 To some extent, metabolic syndrome reflects the diet and lifestyle of patients and is closely related to the occurrence and development of prostate cancer. In addition, Vascular endothelial growth factor (VEGF) as a kind of multi functional cytokine works through specific role in endothelial cells.It can promote endothelial cell proliferation, migration, and increase Vascular permeability. And VEGF can be induced in the body for blood vessel growth, angiogenesis, is closely related to tumorigenesis and metastasis. Numerous recent studies have shown that VEGF is closely related to the occurrence and development of prostate cancer and metabolic syndrome.5 In this paper, multiple physiological and pathological mechanisms of VEGF and metabolic syndrome associated with prostate cancer are reviewed.